Monetary policy without money: Hamlet without the Ghost - David Laidler (The University of Western Ontario, Department of Economics, 2003)
Today' standard model of monetary policy has aggregate demand responding directly to an interest rate under the central bank's control, and ignores the role played by the quantity of money in the transmission mechanism. Even though monetary policy is usually aimed at controlling price level behaviour, and the price level is appropriately modelled as being determined by the interaction of the supply and demand for money, it is going too far to characterise this standard model as Hamlet without the prince. Canadian experience shows that the current framework has worked too well, and its predecessor, based on money growth targeting, worked too badly for this to be fair. Nevertheless, inflation is a monetary phenomenon, and monetary aggregates continue to have useful leading indicator properties. These facts, among others, suggest that a theory of monetary policy which pays explicit attention to the money supply permits a coherent understanding of monetary policy issues. The neglect of money by current approaches leads to a fragmented analysis of monetary policy, just as the omission of the Ghost's demand for vengeance from a production of Hamlet would undermine the play's coherence.
Keywords: 330; Geldpolitik; Inflation Targeting; Transmissionsmechanismus; IS-LM-Diagramm